Incorporating School Culture in Character Education Evaluation: The Development, Validity and Reliability Testing of the “CHILDREN” Character Assessment - Ni Luh Sekar Astuti; Edi Istiyono; Widihastuti Widihastuti (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of character assessment instruments can be derived from the school culture which is arranged in the curriculum at the education unit level. The purpose of this study was to develop and simultaneously test the validity and reliability of a character assessment instrument in the form of a character survey to evaluate character education in the Cooperation Education Unit (SPK) based on school culture. The ADDIE development model was used in developing the character assessment instrument. The product was extensively tested on 200 students from one SPK school, and the data were processed using IBM SPSS 25 for Windows and LISREL 8.80. Using various validity tests on the 25 statement items, it was found that: (1) in the content validity test, 22 (88%) statement items had very good validity, and 3 (12%) statement items had good validity, (2 ) in the construct validity test, it was obtained that all statement items can measure the construct and meet the specified goodness of fit criteria, (3)  in the empirical validity test, the minimum value of rh is 0.201 and is greater than rt (0.138) so that the instrument can be declared as valid, and (4) under the reliability test using Cronbach’s Alpha as a metric, the instrument obtained a value of 0.943 or very high. Based on these results, it can be concluded that the character survey instrument developed is feasible to be used in evaluating school culture-based character education.